2016
DOI: 10.1111/odi.12434
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of information on mouth (oral) cancer

Abstract: Healthcare professionals, academic institutions, and professional organizations have a responsibility for improving the content of YouTube(™) about mouth cancer by uploading useful videos, and directing patients to reliable information sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
222
3
29

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(306 citation statements)
references
References 22 publications
10
222
3
29
Order By: Relevance
“…Concernedly, the quality of videos was also very disappointing when they involve life‐threatening oral conditions, such as oral cancer. A recent investigation demonstrated that only 7.6% of the analysed videos showed useful information on oral cancer, whereas more than 50% were considered either slightly useful, not useful, or even misleading, and, in agreement with our study, they found that videos describing personal experiences were the most viewed …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Concernedly, the quality of videos was also very disappointing when they involve life‐threatening oral conditions, such as oral cancer. A recent investigation demonstrated that only 7.6% of the analysed videos showed useful information on oral cancer, whereas more than 50% were considered either slightly useful, not useful, or even misleading, and, in agreement with our study, they found that videos describing personal experiences were the most viewed …”
Section: Discussionsupporting
confidence: 92%
“…Although the use of social media, such as YouTube™, may have a positive impact on professional networking and education, patient care and education and organisational promotion, they are not exempt from potential dangers, such as poor quality of information, damage of professional image, breaches of patient privacy, or licensing and other legal issues . Therefore, there is an urgent need to screen the source of these videos in order to improve the content of YouTube™ videos as has been previously proclaimed from within other fields of health care …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viewers' interaction was calculated using the following interaction index and viewing rate formulas, respectively: 13 number of likes À number of dislikes total number of views 3 100% ;…”
Section: Methodsmentioning
confidence: 99%
“…Hassona et al carried out a study examining the YouTube videos related with oral cancers during which the videos uploaded by professional associations and healthcare professionals were compared as a result of which it was determined that the videos uploaded by individuals users were less useful (20). Serinken et al carried out a study examining the YouTube videos on kidney stones in which it was determined that the videos uploaded by hospitals were more useful in comparison with videos uploaded by physicians and other healthcare professionals (15).…”
Section: Discussionmentioning
confidence: 99%